2004
DOI: 10.1002/ajmg.a.30276
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the phenotype and definition of the deletion in a new patient with ring chromosome 22

Abstract: The clinical phenotype of patients with ring chromosome 22 includes mental retardation with severe language impairment, hypotonia, and dysmorphic facial features. In recent years an increasing number of patients with microscopic as well as cryptic terminal deletion involving band 22q13 have been described and their phenotype shows clinical features overlapping with patients with ring chromosome 22. Loss of DNA in the 22q13.3 region may lead to a clinically recognizable syndrome named "22q13.3 deletion syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
13
0
2
Order By: Relevance
“…Stankiewicz et al ,12 analysing seven ring chromosomes 18 with proven deletion, concluded that, although the effect of “ring instability syndrome” could not be excluded, the phenotypes of their patients correlated with the features characteristic of 18q- and 18p- syndromes as expected by their genotypes. Similarly, Battini et al 13 reported a patient with an unstable ring chromosome 22 deleted for the last 2.5 Mb, having normal stature and clinical features largely overlapping those of distal 22q deletion. Moreover, recent papers have demonstrated that intact ring chromosomes may cause areas of hypopigmentation along the lines of Blaschko as the only sign of ring induced mosaicism,14 or specific features such as a characteristic type of epilepsy and electroencephalographic pattern as reported for several ring (20) chromosomes,15 thus weakening the hypothesis of the “ring syndrome”.…”
mentioning
confidence: 88%
“…Stankiewicz et al ,12 analysing seven ring chromosomes 18 with proven deletion, concluded that, although the effect of “ring instability syndrome” could not be excluded, the phenotypes of their patients correlated with the features characteristic of 18q- and 18p- syndromes as expected by their genotypes. Similarly, Battini et al 13 reported a patient with an unstable ring chromosome 22 deleted for the last 2.5 Mb, having normal stature and clinical features largely overlapping those of distal 22q deletion. Moreover, recent papers have demonstrated that intact ring chromosomes may cause areas of hypopigmentation along the lines of Blaschko as the only sign of ring induced mosaicism,14 or specific features such as a characteristic type of epilepsy and electroencephalographic pattern as reported for several ring (20) chromosomes,15 thus weakening the hypothesis of the “ring syndrome”.…”
mentioning
confidence: 88%
“…Battini et al [2004] presented a patient with a ring 22 chromosome who demonstrated hypotonia, speech impairment, mental retardation, unusual behavior and dysmorphic features. FISH analysis confirmed a distal deletion approximately 2.5 Mb in size.…”
Section: Review Of Cases From the Literaturementioning
confidence: 99%
“…To determine whether it is also a common disorder in other ring chromosomes, we reviewed epilepsy frequencies in a total of 403 cases with ring chromosomes including 22 autosomes and X chromosome (Fig. 3) [Palka et al, 1986;Fagan et al, 1988;MacDermot et al, 1990;Matalon et al, 1990;Freyberger et al, 1991;Calabrese et al, 1994;Migliori et al, 1994;Lurie, 1995;Flejter et al, 1996;Lanzi et al, 1996;Wahlstrom et al, 1996;Conte et al, 1997;Cutenese et al, 2000;Rodriguez et al, 2000;Tonk et al, 2000;Barajas-Barajas et al, 2001;Dee et al, 2001;Stankiewicz et al, 2001;He et al, 2002;Muroya et al, 2002;Urban et al, 2002;van Karnebeek et al, 2002;Concolino et al, 2003;Ishmael et al, 2003;Morimoto et al, 2003;Parmar et al, 2003;Shashi et al, 2003;Battini et al, 2004;Bedoyan et al, 2004;Le Caignec et al, 2004;Leppig et al, 2004;Rope et al, 2004;Tumer et al, 2004;Zhang et al, 2004;Alkuraya et al, 2005;Nishiwaki et al, 2005]. Only ring chromosomes 14, 17, and 20 are strongly associated with seizure disorders.…”
Section: Seizure Disorder and Ring Chromosomementioning
confidence: 99%